Teks Ucapan Yang Hormat Profesor Dato’ Dr. Daing Nasir Ibrahim Naib Canselor Universiti Malaysia Pahang Sempena Opening Ceremony of University to Industry Career Fair 2016 - Pejabat, Naib Canselor UMP (Universiti Malaysia Pahang, 2016)
First and foremost, it gives great pleasure in welcoming all of you this afternoon to this auspicious occasion that marks the commencement of University to Industry Career Fair 2016.